1.4k views
1 vote
-4(2x - 1) = -6(x + 2) - 2.

User Oya Canli
by
5.1k points

2 Answers

4 votes

Answer:

2

Explanation:

This is our equation-

-4(2x-1)=-6(x+2)

We are trying to isolate x in a side, but first, we must multiply the numbers in between the brackets. A negative number multiplied by a positive number gives a negative number, and a negative times a negative is positive, so-

-8x·4=-6x+(-12)

Now we have to multiply -8x times 4

-32x=-6x-12

Now we isolate x-

-24x=-12

We divide and get the final result of x=2

x=2

User DrSvanHay
by
5.3k points
5 votes

Answer:

x=9

Step-by-step explanation−4(2x−1)=−6(x+2)−2

(−4)(2x)+(−4)(−1)=(−6)(x)+(−6)(2)+−2(Distribute)

−8x+4=−6x+−12+−2

−8x+4=(−6x)+(−12+−2)(Combine Like Terms)

−8x+4=−6x+−14

−8x+4=−6x−14

Step 2: Add 6x to both sides.

−8x+4+6x=−6x−14+6x

−2x+4=−14

Step 3: Subtract 4 from both sides.

−2x+4−4=−14−4

−2x=−18

Step 4: Divide both sides by -2.

−2x

−2

=

−18

−2

x=9

User Leeor
by
5.1k points